EFFICIENCY OF THE DRUG MELDOVENS MAX (MELDONIUM DIHYDRATE AND ARGININE HYDROCHLORIDE) IN THE TREATMENT OF ELDERLY PATIENTS WHO HAVE SUFFERED MYOCARDIAL INFARCTION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In elderly patients with coronary artery disease, Meldovens Max resulted in a decrease in ischemic episodes (–60%), improved physical endurance (CMT +6.5%), normalization of lipid metabolism, and decreased inflammation. Kidney function did not change. The drug demonstrated efficacy and safety as part of rehabilitation therapy.